Predicting "springback" using 3D surface representation techniques: A case study in sheet metal forming. Issue 1 (January 2015) - El Salhi, S.; Coenen, F.; Dixon, C.; Khan, M.S.
Highlights Three generic 3D surface representation techniques are proposed. A framework for using the representations for classifier generation is described. A complete analysis of the representations in the context of classification. Statistical significance testing is presented with respect to the reported results.